1979
DOI: 10.1113/jphysiol.1979.sp012882
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation by cyclic GMP of sodium efflux in barnacle muscle fibres.

Abstract: SUMMARY1. The ouabain-insensitive Na efflux in barnacle muscle fibres is promptly stimulated by injection of cyclic GMP. The minimal effective injected concentration is found to be about 10-7 M. This effect of cyclic GMP could not be mimicked by injecting 5'-GMP.2. External application of ouabain (104 M) to fibres not pretreated with ouabain during the stimulatory response to cyclic GMP causes some inhibition of the Na efflux indicating that cyclic GMP does not cause appreciable inhibition of the Na: K pump.3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1981
1981
1994
1994

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
(26 reference statements)
1
6
0
Order By: Relevance
“…Similar observations have been made with cyclic AMP (Bittar, Chambers & Schultz, 1976) and with cyclic GMP (Bittar & Sharp, 1979).…”
Section: Effect Of Ouabain Following Gtp Injectionsupporting
confidence: 73%
See 2 more Smart Citations
“…Similar observations have been made with cyclic AMP (Bittar, Chambers & Schultz, 1976) and with cyclic GMP (Bittar & Sharp, 1979).…”
Section: Effect Of Ouabain Following Gtp Injectionsupporting
confidence: 73%
“…Lack of dependence on external Na of the response to GTP It has been reported that the response to cyclic AMP ) and cyclic GMP (Bittar & Sharp, 1979) is completely independent of external Na when lithium is used as an Na substitute. It has also been reported that the response to high K is only partly dependent on external Na (Sharp & Bittar, 1980).…”
Section: Effect Of Ouabain Following Gtp Injectionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this interpretation assumes that these agents act in a highly specific manner and do not interfere with normal functioning of other systems that might be involved in the response to raised [K]o. In order to test the possibility that verapamil prevents the response to K depolarization by a means other than blocking the voltage-dependent Ca z + channels, the following experiment was carried out: cyclic GMP, which, in barnacle muscle fibers causes a stimulation of the ouabain-insensitive Na efflux that is dependent on external Ca 2+ but does not involve a change in membrane potential (Bittar & Sharp, 1979), was injected into fibers following external application of 10-4M verapamil. In verapamil-treated fibers injection of 10-3 M cyclic GMP caused an average stimulation of the ouabain-sensitive Na efflux of 67.2+13.2%, n=5.…”
Section: (I) the Effect Of Ca Z +-Channel Blocking Agentsmentioning
confidence: 99%
“…The method of membrane potential measurement was essentially as described by Bittar and Sharp (1979). In the studies presented here the electrode tip was positioned ~ 1 cm below the tip of the cannula in order to avoid penetration of the sarcolemma by the electrode when contraction of the fiber occurred following exposure to elevated [K]o.…”
Section: Em Measurementsmentioning
confidence: 99%